Comparative wear tests of ultra-high molecular weight polyethylene and cross-linked polyethylene - Harsha A.P.; Joyce T.J. (My University, 2025)
Wear particle-induced osteolysis is a major concern in hip implant failure. Therefore, recent research work has focussed on wear-resistant materials, one of the most important of which is cross-linked polyethylene. In view of this, the objective of this study was to compare the in vitro wear performance of cross-linked polyethylene to traditional ultra-high molecular weight polyethylene. In order to mimic appropriate in vivo conditions, a novel high-capacity wear tester called a circularly translating pin-on-disc was used. The results of this in vitro study demonstrated that the wear rate for crosslinked polyethylene was about 80% lower than that of conventional ultra-high molecular weight polyethylene. This difference closely matches in vivo results reported in the literature for total hip replacements that use the two biopolymers. The in vitro results were also verified against ASTM F732-00 (standard test method for wear testing of polymeric materials for use in total joint prostheses). The 50-station circularly translating pin-on-disc proved to be a reliable device for in vitro wear studies of orthopaedic biopolymers. © IMechE 2012.